LABOR CONDITIONS AT MINING AND METALLURGICAL ENTERPRISES AND THEIR INFLUENCE ON THE HEALTH OF BASIC PROFESSIONAL WORKERS - Khamdamov, J.O.; Voronina, N.V. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The analysis of the current state of working conditions at mining and metallurgical enterprises is given. A set of harmful factors of labor for the main occupational groups that determine the development of occupational diseases is specified and promising hygienic directions for their reduction are identified